Aplikasi Transduser Ultrasonik Jenis Immersion Transducer Untuk Karakteristik Media Cair Dan Pengukuran Tingkat Kekasaran Permukaan Beton - Sugito, Heri; Suryono, Suryono; Layla, Diana (BERKALA FISIKA, 2009)
Research of the application of ultrasonics for liquid medium characteristic and measurement of level of surface roughness of concrete have been done using immersion transducer. This purpose of research is to know characteristic some dilutions based on the atanuasi coefficients and measure surface roughness of concretes based on time of flight. In this research applied by ultrasonic transducer with frequency of 1 MHz. At attenuation method, awakened ultrasonic signal through pulse generator and connected at transmitter transducer. Ultrasonic wave which transmitted through liquid medium will experience received finite attenuation of receiver. Media liquid which applied is oil and cooking oil. At method time-of-flight, measurement done with object scan which turned around counted 200 rotation apply motor stepper. Object which applied as component of test that is concrete. Reason of selec,choose it this specimen is to minimize attenuation so that will enlarge the bound. Transducer will transmit modulation to object through modulation transmiter and receiver. Result from scanner is presented at CRO ( Cathode Ray Oscilosco). Research result to liquid medium sample showing existence of tendency of increase of attenuation value for ex-oil- and ex-cooking oil if each compared with oil was new and new cooking oil. From measurement of level of surface roughness, obtained by is surface roughness average yield of concrete A ( Radium of a minimum of 10%, and Ra maximum 16%), and concrete B ( Radium of a minimum of 8%, and Ra maximum 17%). This research result give hope that this method can be developed for inspection innoxious at solid and liquid medium. keyword : Ultrasonic, attenuation coefficient, level of crudity, Time of Flight